Analisis Portofolio Optimal pada Saham Perbankan - Abdul Manap (Al-Buhuts, 2022)
The purpose of research is to determine how much influence the optimal portfolio according to risk and stock profit. This study uses a quantitative method with a descriptive approach, using The IDX Composite (IHSG), interest rate of Bank Indonesia Certificate (SBI), and stock price index of banking sector during August-October 2020, establishment of optimal portfolio is analyzed with single index model. The result show from 35 stocks analysed, there are 9 stocks identified as optimal portfolio with 0.3649% return and 1.0055% risk